Impact of climate changes on marine environments - Zielinski, Tymon; Weslawski, Marcin; Kuliński, Karol (GeoPlanet: Earth and Planetary Sciences,, 2015)
This book contributes to the current discussion on global environmental changes by discussing modifications in marine ecosystems related to global climate changes. In marine ecosystems, rising atmospheric CO2 and climate changes are associated with shifts in temperature, circulation, stratification, nutrient input, oxygen concentration and ocean acidification, which have significant biological effects on a regional and global scale. Knowing how these changes affect the distribution and abundance of plankton in the ocean currents is crucial to our understanding of how climate change impacts the marine environment. Ocean temperatures, weather and climatic changes greatly influence the amount and location of nutrients in the water column. If temperatures and currents change, the plankton production cycle may not coincide with the reproduction cycle of fish.  The above changes are closely related to the changes in radiative forcing, which initiate feedback mechanisms like changes in surface temperature, circulation, and atmospheric chemistry.